Hubungan kadar ureum terhadap kejadian mortalitas pasien sirosis di RSUD dr. Doris Sylvanus Palangka Raya - Rejeki, Fransiska Caesaria Silvi; Alexandra, Francisca Diana; Palupi, Didin Retno Endah; Handayani, Septi; Turnip, Oktaviani Naulita (Fakultas Kedokteran Universitas Palangka Raya, 2024)
The mortality rate of liver cirrhosis is increasing globally, including in Indonesia. Child-Turcotte-Pugh score as a widely used scoring system is difficult to performed in all health facilities in Indonesia. Innovative prognostic screening assessment that is more accessible, and accurate, such as ureum levels, is needed. This research aims to analyze the correlation between ureum levels and mortality of cirrhosis patients. It applied analytic observational study with a cross-sectional design. Data were taken from the patient’s medical records who were hospitalized at RSUD dr. Doris Sylvanus Palangka Raya for the period 2020-2022. Statistical analysis using the Chi-Square test. The p-value = 0.004 (p < 0.05) and OR = 4.54 were obtained, it showed that there was a significant correlation between ureum levels and mortality events in patients with cirrhosis, and patients with high ureum levels were 4.54 times more likely to develop mortality than patients with normal ureum levels.